Fetal consequences of maternal antiretroviral nucleoside reverse transcriptase inhibitor use in human and nonhuman primate pregnancy. Issue 2 (April 2015) - Poirier, Miriam C.; Gibbons, Alexander T.; Rugeles, Maria T.; Andre-Schmutz, Isabelle; Blanche, Stephane
<x xml:space="preserve">Abstract</x> Purpose of review Here we present fetal genotoxicity and mitochondrial toxicity, induced by nucleoside reverse transcriptase inhibitors (NRTIs), in HIV-1-infected pregnant women treated to prevent mother-to-child HIV-1 transmission, and in virus-free pregnant patas monkeys. Recent findings In the offspring of pregnant patas monkeys given human-equivalent NRTI protocols, aneuploidy was found in cultured bone marrow cells taken at birth, 1, and 3 years of age. In some newborn human infants, the offspring of HIV-1-infected mothers given zidovudine (AZT) therapy, aneuploidy, mitochondrial DNA (mtDNA) depletion, morphologically damaged mitochondria, and reduction in cardiac left ventricular muscle were observed. NRTI-exposed human and patas umbilical cords had similar levels of mtDNA depletion and mitochondrial morphological damage. NRTI-exposed patas offspring showed a compensatory increase in heart mtDNA, and a 50% loss of brain mtDNA at 1 year of age. Mitochondrial morphological damage and mtDNA loss were persistent in blood cells of NRTI-exposed infants up to 2 years of age, and in heart and brain from NRTI-exposed patas up to 3 years of age (human equivalent of 15 years). Summary Whereas use of NRTIs in human pregnancy protects many thousands of children worldwide, some HIV-1-uninfected infants born to HIV-1-infected mothers receiving antiretroviral drug therapy sustain toxicities that may have adverse consequences later in life.